2007
DOI: 10.1111/j.1463-5224.2007.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of canine retina and optic nerve function after acute elevation of intraocular pressure: implications for canine glaucoma treatment

Abstract: Purpose To characterize the timing and extent of functional recovery in healthy canine eyes exposed to acute elevation of intraocular pressure (IOP). Methods Acute elevation of IOP was induced in 14 healthy Beagles by elevating IOP above the levels of systolic blood pressure for 60 min (average elevation was between 100 and 160 mmHg). Menace, dazzle and pupillary light reflexes (PLR) were tested at 1, 7, 14 and 28 days post elevation. Optical coherence tomography was used to evaluate retinal thickness preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 51 publications
1
38
0
1
Order By: Relevance
“…Bars represent the median score; boxes show the 25th to 75th percentiles; whiskers represent ±1.58 interquartile range/square root (n). Our glaucoma experimental model has been used before and has proven to be reliable and reproducible [31][32][33]. In the present study the IOP rise was confirmed 1 h after the surgical procedure in animals from both groups.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Bars represent the median score; boxes show the 25th to 75th percentiles; whiskers represent ±1.58 interquartile range/square root (n). Our glaucoma experimental model has been used before and has proven to be reliable and reproducible [31][32][33]. In the present study the IOP rise was confirmed 1 h after the surgical procedure in animals from both groups.…”
Section: Discussionsupporting
confidence: 65%
“…The glaucoma model used is another limitation recognized by the authors. Although this glaucoma experimental model has been used before and has been shown to be reliable and reproducible [31][32][33], glaucoma is a multifactorial and very complex disease. Therefore, combining data from studies using several different glaucoma models is important for understanding the complete picture of EPO ocular neuroprotection in glaucoma disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the absence of full a ophthalmologic examination, i.e., the absence of fundus examination and gonioscopy, the patient qualified as emergency and a decision was taken to perform surgery (Abrams, 2001;Johnsen et al, 2006). At this stage of treatment, the main purpose was to normalise the IOP and protect the optic nerve (Abrams, 2001;Grozdanic et al, 2007;Ofri and Narfstrom, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…1 A fundamental aspect of research study design is the inclusion of a treatment control group, especially when the study involves the evaluation of multiple treatments. Without a control group (i.e.…”
Section: Letter To the Editormentioning
confidence: 99%